2013
DOI: 10.5772/54560
|View full text |Cite
|
Sign up to set email alerts
|

Research Advancements in Humanoid Compression Garments in Sports

Abstract: The utilization of sport-related compression garments has attracted a great deal of attention from among Sports Science scholars. The function of the garments, such as to maintain muscle functions, reduce sports injuries and improve athletic performance, has been an issue of debate since the beginning of the new century. In this study, a number of methods including a literature review, logical analysis and mathematical statistics, are used to analyse earlier compression garments research, which can be found by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Moreover, in the research of accuracy performance of archers, better accuracy and lower heart rate occur at the same time, based on a comparison between experienced archers and inexperienced archers [18]. However, the mechanism behind the physiological and biochemical responses of wearing CGs still remain unclear [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the research of accuracy performance of archers, better accuracy and lower heart rate occur at the same time, based on a comparison between experienced archers and inexperienced archers [18]. However, the mechanism behind the physiological and biochemical responses of wearing CGs still remain unclear [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in accordance with other studies that reported a decreased physiological cost while performing submaximal endurance exercise when wearing CGs. 7,16 The decrease of physiological demand while exercising is extremely desirable, as this may lead to an increase in exercise capacity and muscle efficiency. 6,17 In addition, previous studies have reported that CGs provided participants with increased kinesthetic and proprioceptive awareness leading to an increase in running efficiency, resulting in a decrease in the metabolic cost of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…6,17 In addition, previous studies have reported that CGs provided participants with increased kinesthetic and proprioceptive awareness leading to an increase in running efficiency, resulting in a decrease in the metabolic cost of exercise. 16,17 The combination of the lower metabolic energy cost and the possible ergogenic effect exerted on the exercising limbs may explain the decrease in caloric expenditure during sub-maximal exercise. 22 For recreational and athletic competitors, it is not only the ability to express power, but also sustaining it may ultimately determine success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the progress of time and the development of technology, the high-tech badminton equipment takes an increasingly important role in general itness and athletics [1]. Badminton has been attracted much attention, especially after the Barcelona Olympic Games in 1992 [2].…”
Section: Introductionmentioning
confidence: 99%